Wafer-sized polycrystalline diamond photodetector planar arrays for solar-blind imaging. Issue 16 (7th April 2022) - Zhang, Zhen-Feng; Lin, Chao-Nan; Yang, Xun; Zang, Jin-Hao; Li, Kai-Yong; Lu, Ya-Cong; Li, Yi-Zhe; Dong, Lin; Shan, Chong-Xin
Abstract : A high-quality 2-inch polycrystalline diamond was prepared by MPCVD technique. Photodetector planar arrays were then fabricated from the polycrystalline diamond. Clear solar-blind images have been obtained using the arrays as the sensing unit. Abstract : In this work, a wafer-sized high-quality polycrystalline diamond is prepared using microwave plasma chemical vapor deposition. Solar-blind photodetector arrays with 6 × 6 cells are demonstrated with the polycrystalline diamond. The photodetector array shows good uniformity and stability, a responsivity of 255 mA W −1 at a wavelength of 218 nm and at a bias of 30 V, and a relatively fast response speed (1.2 ms/0.51 ms). Using the planar photodetector array as the sensor unit of an imaging system, clear images can be obtained. This is the first report for photodetector planar arrays based on polycrystalline diamond. Our results indicate that polycrystalline diamond may be used to develop large-area optoelectronic devices.